You are on page 1of 2

.........................

______________________________________________________________
) A( x1 , y1 ) , B( x2 , y2
) A( -3 , 2 ) , B( 1 , 5

= AB

(x2 x1 )2 +( y2 y1)2

) C(x , y AB

= (1AB

AB ) (2C(x , y
x2 + x1
=x
2
y2 + y1
= y
2

( C(x , y
( C(x , y


AB

A 2:3

AB

A
m:n
mx2 + nx1
= x
m+n
my2 + ny1
= y
m+n

( B ( -1 , 4 ) A ( 4 , -3 ( C ( x , y AB
3BC = 2AC
) 7) A ( 2 , -5 ) , B ( -3 , 2
( C ( x , y AB B 3:2
)8
( C ( 5 , -2 ) , B ( 3 , -4 ) , A ( 1 , -6
:
(1 A BC ****
(2 B CA ****

(3 C AB ****
)8
- = X
- = Y
- =
- =
- ) ( 1 , 3- ) , ( 4- , 3- .............
- ) ( 2 , 1- ) , ( 2 , 4 .............
- X 60 .............
- = 1-
(A(-3,2) B(1,5

= 1) AB
2) C (x, y) AB
)3) C (x, y
)4) C (x, y
= 5) mAB

= ml3
= ml1

= ml1
= ml2